If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4x + -12) = 8x + 9 Reorder the terms: 6(-12 + 4x) = 8x + 9 (-12 * 6 + 4x * 6) = 8x + 9 (-72 + 24x) = 8x + 9 Reorder the terms: -72 + 24x = 9 + 8x Solving -72 + 24x = 9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -72 + 24x + -8x = 9 + 8x + -8x Combine like terms: 24x + -8x = 16x -72 + 16x = 9 + 8x + -8x Combine like terms: 8x + -8x = 0 -72 + 16x = 9 + 0 -72 + 16x = 9 Add '72' to each side of the equation. -72 + 72 + 16x = 9 + 72 Combine like terms: -72 + 72 = 0 0 + 16x = 9 + 72 16x = 9 + 72 Combine like terms: 9 + 72 = 81 16x = 81 Divide each side by '16'. x = 5.0625 Simplifying x = 5.0625
| 13+4=-17 | | x^3-7x^2-6x-1=0 | | 4y+2(y-2)=8 | | 2x+(1-x)=4 | | 2y+6(y+3)=32 | | 52*500= | | 9x+1+7x+3=180 | | 2z+5y=8 | | X+8(x+2)=52 | | (2x*2x)+(5x+13)*(5x+13)=(6x+8)*(6x+8) | | -4+5(5r+6)=-49 | | 2x+3xy= | | 8+8(4x+5)=-48 | | 10r+3(-1+10r)= | | 3n+4(4n+4)=-22 | | 6x^2-24x+9=0 | | 4(2x+5)=2(3x-2) | | 3(1+4y)= | | -3+6.3=-14.4 | | 8p-3(1-7p)=32 | | 5n+7=-41 | | 4(n-7)-8n=-60 | | X+0.0675x=2668.75 | | n-11=4 | | 7x-2(7x-5)=-39 | | 6h+(-10)=32 | | x+3x-16=228 | | f(x+8)=9x+7 | | 34=(4x+30) | | 9x-104=-3x+40 | | 4x^2-112x=0 | | -15=(15x+30) |